2017
DOI: 10.1016/j.diabres.2017.02.033
|View full text |Cite
|
Sign up to set email alerts
|

Social economic costs of type 1 diabetes mellitus in pediatric patients in Spain: CHRYSTAL observational study

Abstract: T1DM amongst pediatric patients incurs in considerable societal costs. Informal care represents the largest cost category.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 31 publications
0
12
1
Order By: Relevance
“…69% of the children reported a diabetic complication. Poor glycaemic control may cause episodes of hypoglycaemia which can affect developing nervous system and children with diabetes mellitus who are aged less than 7 years are at risk of cognitive dysfunction (10). In this study 74% of the children who had HbA1c had a result ≥7.5% indicating poor metabolic control which is contrary to a study in Spain where 60% of the children had a HbA1c < 7.5% (López-Bastida et al, 2017).…”
Section: Discussioncontrasting
confidence: 69%
“…69% of the children reported a diabetic complication. Poor glycaemic control may cause episodes of hypoglycaemia which can affect developing nervous system and children with diabetes mellitus who are aged less than 7 years are at risk of cognitive dysfunction (10). In this study 74% of the children who had HbA1c had a result ≥7.5% indicating poor metabolic control which is contrary to a study in Spain where 60% of the children had a HbA1c < 7.5% (López-Bastida et al, 2017).…”
Section: Discussioncontrasting
confidence: 69%
“…Because of the rapid developments in the innovation of the treatment of T1DM [ 19 22 ] with an increasing use of high-tech devices, the costs of treating T1DM in children are likely to increase further in the coming years. Data from adults with diabetes suggest that more expenditure is needed for general care not directly related to diabetes compared to diabetes related care [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…We randomly selected 12 centers across Spain and the researchers randomly selected patients fulfilling the inclusion criteria. More information about the study population selection can be found in L opez-Bastida and co-authors 22 .…”
Section: Study Populationmentioning
confidence: 99%